Global dynamics of the Earth : applications of viscoelastic relaxation theory to solid-earth and planetary geophysics /: applications of viscoelastic relaxation theory to solid-earth and planetary geophysics. (2016) - Sabadini, R; Vermeersen, Bert, 1961-; Cambiotti, Gabriele
No abstract available